Exploring innovative models of surgical treatment for rectal cancer - LI Xinxiang, LUO Dakui (Zhongguo aizheng zazhi)
In recent years, the surgical treatment model for rectal cancer has undergone profound changes. The therapeutic goal has gradually shifted from single tumor radical resection to balancing functional preservation, and the therapeutic concept has transformed from merely emphasizing surgical techniques to attaching importance to comprehensive treatment. Especially in the treatment of low rectal cancer, the neoadjuvant therapy model has been continuously optimized. For patients with good tumor regression after neoadjuvant therapy, “watch and wait” and transanal local excision have become important optional strategies. This not only avoids some severe surgery-related complications but also maximizes the preservation of patients’ organ functions, bringing a qualitative leap in their quality of life. This treatment strategy is gradually expanding from locally advanced low rectal cancer to relatively early-stage low rectal cancer. In terms of surgical techniques, based on the traditional intermediate approach of “first plane, then vessels”, the concept of a “vessel-centered” approach is proposed. By managing vessels first and then expanding the plane, it enables thorough dissection of lymph nodes at the root of the inferior mesenteric artery while preserving the left colic artery. With the aid of dual-fluorescence intraoperative navigation technology [indocyanine green (ICG) fluorescence and intraoperative real-time imaging system (IRIS) ureter fluorescence imaging], real-time visualization of lymph nodes and ureters is achieved, ensuring the completeness of lymph node dissection and helping to reduce the risk of ureteral injury. The angulation-free double anastomosis technique used during surgery effectively reduces the incidence of anastomotic leakage and improves surgical safety. For patients with high-risk factors for anastomotic leakage, intestinal stent bypass is expected to replace the traditional prophylactic end ileostomy, thus avoiding complications associated with prophylactic end ileostomy and the trauma caused by secondary stoma closure. In general, the development trend of surgical treatment for rectal cancer is to minimize patient trauma, preserve organ functions, and improve quality of life under the premise of ensuring oncological efficacy, promoting the development of surgical techniques towards standardization and precision to maximize patients’ perioperative safety.